Investigating users' reactions to surprising products. (July 2020) - Becattini, Niccolò; Borgianni, Yuri; Cascini, Gaetano; Rotini, Federico
Abstract : The study of surprising product features is crucial for designing products that potentially trigger attention and curiosity. Through a tailored questionnaire, this study gathered reactions from 100 respondents to solutions which were considered to be surprising. The data about surprise emergence and its modalities were processed using a situated FBS-based cognitive framework, shifted to the perspective of the user/observer. Data analysis shows that FBS variables and the related cognitive processes are suitable for describing similarities and differences in the reasoning path of users when surprise emerges. This confirms that individually pre-conceived expectations are crucial to surprise emergence and that these expectations relate to functional, behavioural or structural variables with similar mechanisms that depend on thinking processes triggered by product features. Highlights: Surprise is a candidate game changer in creative design. 100 respondents answered a questionnaire about 3 surprising products each. Function-Behaviour-Structure links explain surprised reactions and cognition. Different FBS design variables feature distinct modalities of surprise emergence. The results pave the way for the development of "design for surprise" guidelines.